Experimental Study Conducted Rendahsetelah Tenacity Carbon Steel Heat Treatment Austempering - Wijaya R D (Bandar Lampung University (UBL), 2017)
The principle of this Austempering heat treatment is done by heating the steel to austenite tempratur then quenching the hot water bath salts ± 250-550 ° C and held at that time long enough so that the austenite transformed into bainite entirety. If the eutectoid steel is cooled rapidly in the austenite phase to a temperature between 250- 550 ° C and held at that temperature interval (isothermal) will be formed called bainite microstructure according to the name of the inventor, Dr. EC Bain. Bainite microstructure is the result of non-lamellar eutectoid reaction while perlite produced from lamellar eutectoid reaction. Bainite is a microstructure that is a mixture of ferrite phase and cementite (Fe3C). At a temperature of 350-550 ° C will be formed bainite top (upper bainite) while at 250-350 ° C will be formed under the bainite (lower bainite). In this study material used for heat treatment of austempering is low carbon steel with a solution of salt water quenching media. In this study austempering process carried out at a temperature of 300, 350, and 400 ° C with a holding time of 30 minutes. The results of this study indicate if low carbon steel austempering process is carried out hardness values decreased, namely from 144 to 116 at a temperature of 400 ° C, so the higher the austempering tempratur lower hardness value